Neutrophil-Lymphocyte Ratio as a Predictor of Ulcer Severity in Type 2 Diabetes - Prima Budi Prayogi; Prima Kharisma Hayuningrat; Suharto Wijanarko; Hari Wujoso (Open Access Indonesian Journal of Medical Reviews, 2025)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder with increasing global prevalence, frequently complicated by foot ulcers. These ulcers present a significant burden, often leading to amputation and increased mortality. The neutrophil-lymphocyte ratio (NLR), a readily available marker of systemic inflammation, has emerged as a potential prognostic indicator in various diseases. This study investigated the correlation between NLR and the severity of foot ulcers in patients with T2DM. A retrospective, cross-sectional study was conducted, analyzing data from 60 patients with T2DM and foot ulcers admitted to Dr. Moewardi General Hospital, Surakarta, between January 1st, 2022, and December 31st, 2023. NLR was calculated from routine complete blood counts. Ulcer severity was graded using the Meggitt-Wagner classification. Statistical analysis included Spearman's rank correlation and Kruskal-Wallis tests. Our study found a significant correlation observed between NLR and ulcer severity (ρ = 0.524, p < 0.001), with NLR values increasing with ulcer grade. Amputation was significantly associated with ulcer severity (p=0.009). In conclusion, NLR is a valuable and readily available biomarker for assessing the severity of foot ulcers in patients with T2DM. Elevated NLR is associated with more severe ulcers and a higher likelihood of amputation. Incorporating the assessment of NLR into the routine evaluation of patients with diabetic foot ulcers can aid in risk stratification and guide clinical management.